P9 Validation of the adjusted global antiphospholipid syndrome score and correlation with extra-criteria manifestations. (23rd March 2020) - Uludag, Omer; Bektas, Murat; Cene, Erhan; Sahinkaya, Yasemin; Gul, Ahmet; Ocal, Lale; Inanc, Murat; Artim-Esen, Bahar
Abstract : Background/Purpose: Adjusted global antiphosholipid syndrome score (aGAPSS) is the simplified version GAPSS that was recently developed to assess thrombotic risk by the consideration of antiphospholipid antibody (aPL) profile and conventional cardiovascular risk factors. The aim of this study was to evaluate the validity of the aGAPSS in predicting thrombosis and extra-criteria manifestations in our antiphospholipid syndrome (APS) cohort. Methods: Ninety-eight patients with APS were classified according to clinical manifestations as vascular thrombosis (VT), pregnancy morbidity (PM) or both (VT+PM). The aGAPSS was calculated as defined before. Arterial hypertension and hyperlipidemia definitions were made according to the ESC/ESH ve NCEP/ATP III guidelines, respectively. Results: Demographic, laboratory and clinical characteristics of patients are summarized in table 1 . Mean aGAPSS was calculated as 10.2 ± 3.8. Significantly higher aGAPSS values were seen in VT ( n =58) and VT+PM ( n =29) compared to PM ( n =11) (mean aGAPSS 10.6 ± 3.7 vs 7.3 ± 2.9, P =0.005; 10.5 ± 4 vs 7.3 ± 2.9, P =0.01, respectively). AUC demonstrated that aGAPSS values ≥ 10 had the best diagnostic accuracy for thrombosis (AUC: 0.71, sensitivity: 0.52, specificity: 0.91, P =0.01). Higher aGAPPS values were also associated with recurrent thrombosis (mean aGAPSS 11.5 ± 3.7 vs 9.9 ± 3.6, P =0.04). Regarding extra-criteria manifestations, patients with livedo reticularis ( n =11) and APS nephropathy ( n =9) had significantly higher aGAPSS values (mean aGAPSS 12.9 ± 3.4 vs 9.9 ± 3.7, P =0.02; 12.4 ± 2.9 vs 10 ± 3.8, P =0.04, respectively). Conclusion: Our results suggest that patients with higher aGAPSS values are at higher risk for developing vascular thrombosis (either single or recurrent) and extra-criteria manifestations, especially livedo reticularis and APS nephropathy.